OPTIMIZING STATE EXPENDITURE: AN ACCOUNTING PERSPECTIVE IN THE CONSTRUCTION INDUSTRY - Ardhanari, Margaretha; Viphindrartin, Sebastiana; Widarni, Eny Lestari; Bawono, Suryaning (Jurnal Akuntansi Multiparadigma, 2025)
-